The Transmission of Global and Regional Extremism in Indonesia - Syauqillah, Muhamad; Faton, Marella Al (UI Scholars Hub, 2019)
Salafi Jihadi has been widely accused of being the actor behind terrorist acts in various parts of the world. In Indonesia, acts of terror are generally carried out by parties who have relations with the Salafi movement who have transmissions at the regional and global levels. The Salafi movement literature originating from the Middle East, accompanied by political dynamics and conflict in the Middle East, has become the light of the radical movement in Indonesia. This study uses qualitative methods with a literature study approach and in-depth interviews. Analysis of the transmission of extremism is carried out using transnational theory and social movements. The results show that the transmission of extremism that occurred in Indonesia was caused by the idea of Salafi Jihadi and the events of the conflict in the Middle East.